Status Kesehatan Pasar Ditinjau Dari Aspek Sanitasi Dan Perilaku Hidup Bersih Sehat (PHBS) Pada Pasar Ciputat dan Pasar Modern BSD Kota Tangerang Selatan - Rusman Efendi; Jihan Nada Alya Syifa (HB PRESS, 2019)
ABSTRACT The less market seen from the aspect of good sanitation and health behaviour of traders, managers and visitors can be a source of perkembangbiakkan and the spread of the disease. This can occur as a result of the Junk pile and all types of shit that has decayed, the absence of sewer/drainage and inadequate building conditions, conditions that are less healthy can be a flow of transmission of diseases from one person keorang another either through direct or indirect contact. One way to break the direct or indirect contacts that can occur in a market environment that is need for the implementation of a good market environment sanitation in accordance with the guidelines of the healthy market Kepmenkes Number 519/Menkes/SK/VI/2008. The purpose of this research is to know the health status of the market in terms of Sanitation and market aspects of Ciputat and markets Modern BSD. This research was conducted in may 2018. This research is the kind of research kuantitif with a descriptive observational approach by using a cross sectional study design, which is based on checklist No. 519 Kemenkes the year 2008 about the market Healthy. Health status of Ciputat Market aspects of sanitation categorized less with a score of 1484 or 51.5%, yet in the aspect of PHBS Ciputat Market categorized less well with a score of 1400 or 46.7% while Modern market's Health Status in terms of BSD sanitary aspects categorized both by a score of 2500 or 86.8% but in the aspect of Modern market PHBS BSD categorized both by a score of 2350 or 78.3%. The good health status of the Modern market and Ciputat Market BSD assessed aspects of sanitation and clean living and healthy behaviors (PHBS), on the assessment of the two aspects of the modern market of sanitary aspects and PHBS, market manager for Advice to undertakings leasehold improvements to market better, and need to be held or the educational approach to health promotion in the form of a media poster about the importance of clean living and healthy behavior in the market environment and sanitation hygiene training for traders and workers to improve public health degrees